Outcome Following Hemorrhage From Cranial Dural Arteriovenous Fistulae: Analysis of the Multicenter International CONDOR Registry. Issue 10 (October 2021) - Koch, Matthew J.; Stapleton, Christopher J.; Guniganti, Ridhima; Lanzino, Giuseppe; Sheehan, Jason; Alaraj, Ali; Bulters, Diederik; Kim, Louis; Fox, W. Christopher; Gross, Bradley A.; Hayakawa, Minako; van DijK, J. Marc C.; et al.
Abstract : Background and Purpose: Dural arteriovenous fistulae can present with hemorrhage, but there remains a paucity of data regarding subsequent outcomes. We sought to use the CONDOR (Consortium for Dural Arteriovenous Fistula Outcomes Research), a multi-institutional registry, to characterize the morbidity and mortality of dural arteriovenous fistula–related hemorrhage. Methods: A retrospective review of patients in CONDOR who presented with dural arteriovenous fistula–related hemorrhage was performed. Patient characteristics, clinical follow-up, and radiographic details were analyzed for associations with poor outcome (defined as modified Rankin Scale score ≥3). Results: The CONDOR dataset yielded 262 patients with incident hemorrhage, with median follow-up of 1.4 years. Poor outcome was observed in 17.0% (95% CI, 12.3%–21.7%) at follow-up, including a 3.6% (95% CI, 1.3%–6.0%) mortality. Age and anticoagulant use were associated with poor outcome on multivariable analysis (odds ratio, 1.04, odds ratio, 5.1 respectively). Subtype of hemorrhage and venous shunting pattern of the lesion did not affect outcome significantly. Conclusions: Within the CONDOR registry, dural arteriovenous fistula–related hemorrhage was associated with a relatively lower morbidity and mortality than published outcomes from other arterialized cerebrovascular lesions but still at clinically consequential rates. Abstract : Supplemental Digital Content is available in the text.